The tabaqat i akbari of Khawajah Nizamuddin Ahmad : a history of India from the early musalman invasions to the thirty sixth year of the reign of akbar - Khawajah Nizamuddin Ahmad (Low price Publications, 1992)
ast JIL.1=C.1-3 JIL.2=C.1-3 JIL.3=C.1-3